The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1088/1748-3190/11/4/046006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of anguilliform locomotion in fishes studied using simple three-dimensional physical models

Abstract: Physical models enable researchers to systematically examine complex and dynamic mechanisms of underwater locomotion in ways that would be challenging with freely swimming animals. Previous research on undulatory locomotion, for example, has used rectangular flexible panels that are effectively two-dimensional as proxies for the propulsive surfaces of swimming fishes, but these bear little resemblance to the bodies of elongate eel-like swimming animals. In this paper we use a polyurethane rod (round cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In black ghost knifefish swimming, it has been reported numerous complex fin bending patterns including the curling of the rays into the flow, smooth curvatures and sharp peaks (Youngerman et al 2014). In addition, previous studies (Lauder et al 2007, Wen and Lauder 2013, Feilich and Lauder 2015, Lim and Lauder 2016 have observed similar bending and deforming behaviors in other types of fins. In our study, the interaction between the elastodynamic property of the flexible rays, the tensile behavior of the elastic membrane and the surrounding fluid leads to the deflection amplitude for a fullyactuated fin starting from around 6 cm at 0.5 Hz to greater than 8 cm after 4 Hz.…”
Section: Kinematicsmentioning
confidence: 80%
“…In black ghost knifefish swimming, it has been reported numerous complex fin bending patterns including the curling of the rays into the flow, smooth curvatures and sharp peaks (Youngerman et al 2014). In addition, previous studies (Lauder et al 2007, Wen and Lauder 2013, Feilich and Lauder 2015, Lim and Lauder 2016 have observed similar bending and deforming behaviors in other types of fins. In our study, the interaction between the elastodynamic property of the flexible rays, the tensile behavior of the elastic membrane and the surrounding fluid leads to the deflection amplitude for a fullyactuated fin starting from around 6 cm at 0.5 Hz to greater than 8 cm after 4 Hz.…”
Section: Kinematicsmentioning
confidence: 80%
“…Examples of this phenomenon are commonly seen in recent studies of flexible swimming models of aquatic locomotion (e.g. Akanyeti et al, 2017;Alben et al, 2012;Lauder et al, 2012;Lim and Lauder, 2016;Lucas et al, 2015;McHenry et al, 1995) where input motions to the 'head' of a swimming simple model fish result in complex patterns of body bending and fluid flow around and behind the model due to interactions between the fluid and the structure. As another example, a simple model of terrestrial locomotion, the bristlebot (Becker et al, 2014), is designed with flexible toothbrushlike bristles serving as 'legs' that interact with the ground.…”
mentioning
confidence: 90%
“…In an experimental demonstration by Ramananarivo et al [3], an elastic swimmer actuated at the head by the magnetic field was shown to locomote on the free surface with an emergent anguilliform kinematics. In a series of studies by Lauder and coauthors, the effects of frequency and amplitude, body length and stiffness, planform and cross-section shape on the propulsive performance were assessed [4][5][6][7][8][9][10][11][12][13]. This type of artificial swimmer provides us a useful tool for analyzing flow structure and energy efficiency across a wide range of parameter values.…”
Section: Introductionmentioning
confidence: 99%